2020
DOI: 10.7235/hort.20200070
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins in Tree Peony (Paeonia suffruticosa) and Their Relationship with Flower Color

Abstract: Flower color is an important trait of tree peony (Paeonia suffruticosa), an economically important species. The accurate classification of flower color and understanding of the mechanism involved in creating variations in flower color provide the basis of tree peony breeding and genetic research. This study used the International Commission of Illumination Color System, known as CIELAB or CIE L*a*b*, to measure the flower color of 150 cultivars of the Zhongyuan cultivar group of tree peony. Hierarchical cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The flower colors of tree peonies can be divided into nine types: red, pink, yellow, purple, green, white, black, blue, and multi-color. Most research on tree peonies has focused on red, pink, yellow, purple, and multi-color blooms [2][3][4][5][6][7][8][9] and petal blotch [10,11], which are bright and conspicuous, with no prior studies reported on green-colored peonies. There are more than ten cultivars of green flower peonies in China, but all their blooms transition to white or pink upon opening, significantly diminishing their ornamental appeal.…”
Section: Introductionmentioning
confidence: 99%
“…The flower colors of tree peonies can be divided into nine types: red, pink, yellow, purple, green, white, black, blue, and multi-color. Most research on tree peonies has focused on red, pink, yellow, purple, and multi-color blooms [2][3][4][5][6][7][8][9] and petal blotch [10,11], which are bright and conspicuous, with no prior studies reported on green-colored peonies. There are more than ten cultivars of green flower peonies in China, but all their blooms transition to white or pink upon opening, significantly diminishing their ornamental appeal.…”
Section: Introductionmentioning
confidence: 99%